Probiotic Amelioration of Azotemia in 5/6th Nephrectomized Sprague-Dawley Rats - Natarajan Ranganathan; Beena Patel; Pari Ranganathan; Joseph Marczely; Rahul Dheer; Tushar Chordia; Stephen R. Dunn; Eli A. Friedman (The Scientific World Journal)
The present study was to test the hypothesis that selected bacteria instilled into the gastrointestinal tract could help in converting nitrogenous wastes accumulated due to renal insufficiency into nontoxic compounds; thereby, ameliorating the biochemical imbalance. Herein we describe a prospective, blinded, placebo-controlled pilot study, using 5/6th nephrectomized Sprague Dawley rat as a chronic renal failure model. The study group consisted of 36 nephrectomized and 7 non-nephrectomized (control) rats. After two-week nephrectomy stabilization, cohorts of six nephrectomized rats were fed casein-based diet plus one of the following regimens: (A) Control, (B) Placebo (casein-based diet without probiotics), (C) Bacillus pasteurii, (D) Sporolac®, (E) Kibow cocktail, (F) CHR Hansen Cocktail, and (G) ECONORMTM. Subsequently, blood (retro-orbital) and urine (collected for measurements of blood urea-nitrogen and creatinine respectively), body weight and bacterial counts (feces) were obtained at regular intervals. The study end-points were to determine if any of the probiotic dietary supplements facilitated, (1) decreased blood concentrations of uremic toxins, (2) altered renal function, and (3) prolonged survival. After 16 weeks of treatment, regimens C and D significantly prolonged the life span of uremic rats, in addition to showing a reduction in blood urea-nitrogen levels, concluding that supplementation of probiotic formulation to uremic rats slows the progression of azotemia, which may correlate with prolonged life span of uremic rats. Derivative trials of probiotic treatment of larger animals and humans will further assess the potential role of probiotic formulations in delaying the onset and clinical severity of clinical illness at different stages of renal failure.